Development and evaluation of the Acromegaly Symptom Diary - Susan Martin; Randall H. Bender; Alan Krasner; Tonya Marmon; Michael Monahan; Lauren Nelson (Journal of Patient-Reported Outcomes, 2023)
Abstract Background Patient-reported outcome (PRO) measures are important to consider when evaluating treatments, yet there are no PRO measures for patients with acromegaly that have been developed in accordance with US Food and Drug Administration guidance. Acromegaly is a rare, chronic condition caused by hypersecretion of growth hormone. Disease activity is monitored by measurement in serum of growth hormone and insulin-like growth factor-I. The objectives of this research were to develop the Acromegaly Symptom Diary (ASD), establish a scoring algorithm, and evaluate the psychometric measurement properties of the ASD. Methods Semistructured interviews consisting of concept elicitation and cognitive debriefing components were conducted with 16 adult participants with acromegaly. The concept elicitation component identified symptoms important to individuals with acromegaly. The cognitive debriefing component gathered information about the participants’ experience with each proposed item of the ASD, their thought process for answering each question, and their interpretation of the items. The psychometric properties of the draft ASD were then evaluated using data from the ACROBAT Evolve (NCT03792555; n = 13) and ACROBAT Edge (NCT03789656; n = 47) clinical trials. Results The 16 participants from the interviews described ongoing symptoms, with the most frequently reported being joint pain (n = 13) and fatigue (n = 12), followed by swelling (n = 8), headache (n = 7), and mood swings (n = 6), and were able to interpret and understand the ASD items and had no issues with the 24-hour recall period. From data collected in the clinical studies, the psychometric properties of internal consistency (0.91 − 0.80), test-retest reliability with item-level and total ASD scores (> 0.70), baseline construct validity (r ≥ |0.38|) across scales, and responsiveness to change (r = 0.52–0.56) were supported for the ASD. The proposed preliminary threshold range to characterize a meaningful change from the patients’ perspective for the ASD total is a 4- to 6-point change for improvement or worsening out of a total score of 70. Conclusion These findings provide qualitative and quantitative evidence to support the ASD as fit for the purpose of evaluating the symptom experience of patients with acromegaly in clinical trials.